Identifikasi Pelaku Etnomedisin dan Informasi Jenis Tanaman Obat yang Digunakan dan Tumbuh di Provinsi Lampung (Kajian Pengembangan Taman Herbal di Provinsi Lampung Tahun 2017) - Azhari Rangga; Hernita Astuti; Purwoto User; Agus Subowo; Jekvy Hendra (Balitbangda Provinsi Lampung, 2017)
The study of ethnomedicine is basically to understand the health culture from the perspective of society, especially the system of alternative medicine by using medicinal plants that have become tradition of hereditary society. The purpose of this study was to obtain information about personal identity profiles and supporting data of Ethnomedicine actors; formulate information about the types of medicinal plants grown in Lampung Province, provide information about the efficacy and efficacy of medicinal plants based on literature review. The results of this study described the profile of 5 ethnomedicine actors with various types of plants used in Lampung Province of 35 types of medicinal plants, while the rest were obtained from other regions. Output development was the provision of traditional medicinal materials available with target areas and types of plants used to support the needs of traditional health programs and sustainable pharmaceutical industries